Differential expression profiles of lncRNAs and a preliminary study on the mechanism of lncRNA FAM225A in triple seronegative myasthenia gravis - Hao, Yuehan; Chen, Chen; Wang, Bo; Yang, ChunHua; Zhu, Ying; Zhu, Ruixia (Frontiers in Immunology, 2025)
BackgroundTriple-seronegative (Triple-SN) myasthenia gravis (MG) is a subtype of MG, and its diagnosis and treatment are challenging. Our study aims to discover new biomarkers and potential therapeutic targets and explore the preliminary mechanisms of triple-SN MG.MethodsPeripheral blood mononuclear cells (PBMCs) were collected from 15 patients with triple-SN MG who were newly diagnosed with the disease and 15 healthy controls. Various experimental techniques and analysis methods, such as PBMC isolation, microarray analysis, dual-luciferase reporter assay, quantitative real-time polymerase chain reaction (qRT-PCR), cell culture, and transfection, were used.ResultsOur study identified 385 differentially expressed genes (DEmRNAs) and 361 differentially expressed lncRNAs (DElncRNAs) in triple-SN MG. Notably, lncRNA FAM225A, one of the top five downregulated DElncRNAs, was verified to decreased and negatively correlated with the clinical severity of triple-SN MG. Functional enrichment analysis, immune infiltration analysis and further experiments revealed that FAM225A affected the imbalance of Th1/Th2 by targeting hsa-miR-150-5p in the pathogenesis of triple-SN MG.ConclusionsThis study is the first to provide important clues for understanding the pathological mechanism of triple-SN MG, which might contribute to the discovery of novel diagnostic and therapeutic monitoring biomarkers and new targets for the treatment of triple-SN MG.